Effects of shot peening and pre-strain on the fatigue life of dual phase Martensitic and Bainitic steels. (April 2017) - Walker, James; Thomas, Daniel J.; Gao, Yi
Highlights: For both DP600 and FB600, once the steels experience a pre-strain value of 10%, the fatigue performance is dramatically improved across the range of stresses. On average, pre-straining is found to be the best solution for producing the best fatigue resistant AHSS grade. After pre-straining the interstitials remain and restricts the dislocation movement throughout the fatigue test. The 200% coverage induced in shot penning process has produced good fatigue improvement results at the HCF end of the fatigue curves for both steels. Abstract: The effect of shot peening and pre-straining has been investigated as method for enhancing the fatigue life of DP600 and FB600 advanced high strength steel grades in the automotive sector. Investigative work shows significant improvement of the performance of the original grades by introducing cold working in the form of near edge enhancements using shot peening at 200% coverage at an intensity of 0.004–0.008" and via 10% pre-straining. It is the microstructure and deformation properties of the second phase of 10% content Martensite and 9% content Bainite that results in significantly different resulting fatigue lives under different work-hardening regimes.